2022
DOI: 10.1111/gec3.12618
|View full text |Cite
|
Sign up to set email alerts
|

The aesthetic turn in border studies: Visual geographies of power, contestation and subversion

Abstract: In recent years, critical border studies have developed sophisticated concepts and methodologies for exploring the multifaceted spatialities, sociologies and temporalities of contemporary borders. In this article, we consider how the “aesthetic turn” that has gained prominence in the scholarship can further inform thinking in border studies. Specifically, we focus on the role of the visual in the construction as well as subversion of borders, suggesting possible avenues for future critical aesthetics‐engaged r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 169 publications
(164 reference statements)
0
2
0
Order By: Relevance
“…In summary, the passage highlights several ways in which architecture can influence and improve taste (Moosmayer dkk., 2020). These mechanisms include education through media and documentaries, interactive models of taste for users, and the establishment of a shared language for discussing architectural preferences (Moze & Spiegel, 2022). By employing these methods, architecture can play a significant role in shaping and refining public and individual tastes in the field.…”
Section: Resultsmentioning
confidence: 99%
“…In summary, the passage highlights several ways in which architecture can influence and improve taste (Moosmayer dkk., 2020). These mechanisms include education through media and documentaries, interactive models of taste for users, and the establishment of a shared language for discussing architectural preferences (Moze & Spiegel, 2022). By employing these methods, architecture can play a significant role in shaping and refining public and individual tastes in the field.…”
Section: Resultsmentioning
confidence: 99%
“…As a field-based technique, visual methods are widely used, particularly within the social sciences (Rose 2014, Moze and Spiegel 2022. Cities are frequently the settings for the application of critical visual research methods (Tormey 2013, Yap 2021, the interrogation of the influences and impacts of visual objects and for observers to explore how they themselves look, see and interpret them (Speake 2017a).…”
Section: Methodological Approachmentioning
confidence: 99%
“…In the recent years authors have identified the "aesthetic turn" in border studies, particularly with the research of visual representation of borders in photographs, documentary films, videos, as well as maps and other visual objects deployed to visualize the borders (Moze and Spiegel 2022;Kudžmaitė and Pauwels 2020;Boyce 2020;Ellison and Van Isacker 2021). According to Moze and Spiegel, from the perspective of geographical studies, "the aesthetic turn in border studies refers to a variety of empirical, conceptual and methodological interests in prompting attention to how processes of rendering visible/invisible are to be understood" (Moze and Spiegel 2022, 3).…”
Section: O N L I N E F I R S Tmentioning
confidence: 99%